Information Structure in Sign Languages Evidence from Russian Sign Language and Sign Language of the Netherlands - Kimmelman, Vadim (Sign Languages and Deaf Communities [SLDC], 2019)
This book presents a first comprehensive overview of existing research on information structure in sign languages. Furthermore, it is combined with novel in-depth studies of Russian Sign Language and Sign Language of the Netherlands. The book discusses how topic, focus, and contrast are marked in the visual modality and what implications this has for theoretical and typological study of information structure. Such issues as syntactic and prosodic markers of information structure and their interactions, relations between different notions of information structure, and grammaticalization of markers of information structure are highlighted. Empirical studies of the two sign languages also showcase different methodologies that are used in such research and discuss their advantages and disadvantages. The book contains a general introduction to the field of information structure and thus can be used by linguists new to the field.